2019
DOI: 10.1080/10717544.2019.1704943
|View full text |Cite
|
Sign up to set email alerts
|

[12]aneN 3 -based multifunctional compounds as fluorescent probes and nucleic acids delivering agents

Abstract: A series of multifunctional compounds (MFCs) 1a-1e based on 1,8-naphthalimide and [12]aneN 3 building blocks were designed and synthesized. They were used as not only fluorescent probes for recognition of Cu 2þ ions but also as non-viral gene vectors for DNA and RNA delivery. Furthermore, their complexes with Cu 2þ (1-Cu) could also selectively stain lysosome in HeLa cells. In order to achieve high performance multifunctional materials, structure-performance relationship of MFCs 1a-1e was studied. It was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Remarkably, the adamantyl-substituted analogue ( Ad P Pym DI)­FeCl 2 29 reached full conversion within 30 min, to form 4a in >95% selectivity. A challenge in first-row transition-metal-catalyzed alkyne trimerization is suppressing competitive alkyne polymerization pathways, , which lead to apparently high NMR conversions but modest isolated yields of the target products. However, as evident from the mass balance data for 2 (Figure , right), 29 and 35 (see the Supporting Information), no competing alkyne polymerization could be noted.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…Remarkably, the adamantyl-substituted analogue ( Ad P Pym DI)­FeCl 2 29 reached full conversion within 30 min, to form 4a in >95% selectivity. A challenge in first-row transition-metal-catalyzed alkyne trimerization is suppressing competitive alkyne polymerization pathways, , which lead to apparently high NMR conversions but modest isolated yields of the target products. However, as evident from the mass balance data for 2 (Figure , right), 29 and 35 (see the Supporting Information), no competing alkyne polymerization could be noted.…”
Section: Resultsmentioning
confidence: 71%
“…The excellent tolerance of a variety of functional groups gives products suitable for downstream elaboration, for example, by nucleophilic displacement ( 8a and 9a ), deprotection and further functionalization ( 10a , 11a , 13a , and 15a – 17a ), or cross-coupling reactivity ( 8a , 9a , 12a , and 18a ). These products therefore function as useful synthons for targets containing a C 3 -symmetrical arene center. Apart from being atom economical, our Fe-catalyzed methodology provides an advantage over potential one-step routes to access the same substrates (for example, via cross-coupling from 1,3,5-tribromobenzene), where functionalities incorporated in 8 , 9 , 12 , or 18 would be challenging to preserve. The substitution pattern in the immediate vicinity of the CC triple bond plays an important role in selectivity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of transport mechanisms showed that the liposome/DNA complex mainly entered cells in an energy-independent manner. Further research found that [12]aneN 3 compounds modified with naphthalimide can not only be used as gene carriers to deliver nucleic acids, but can also be used as fluorescent probes to identify copper ions and small biological molecules [ 123 , 124 ].…”
Section: Liposome Nanoparticlesmentioning
confidence: 99%
“…In recent years, we have developed a series of rigid‐naphthalimide‐modified lipids 30–33 . We found that the transfection efficiency was improved due to the introduction of rigid naphthalimide.…”
Section: Introductionmentioning
confidence: 99%